Польська преса в протидії російській пропаганді під час окупації Кримського півострова (лютий-квітень 2014) - Шипотілова, Олена Павлівна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The study is examined the issue of the Polish press in the countering Russian propaganda during the occupation of the Crimean Peninsula. The articles of Polish journalists are analyzed the course of the main chronological events in Crimea, gave the definition and nature of the Russian occupation, the term “green men”, advice to the new Ukrainian government on activities in the conditions of Russian aggression. On the pages of Polish newspapers, the number of personnel and military forces transferred by Russia to Crimea, the thorough opinions of well-known representatives of the Ukrainian authorities, intelligentsia and the international community, especially the opinions of the indigenous peoples of the Republic of Crimea regarding the annexation of the territory of the peninsula to the Russian Federation, are highlighted.